Privilege: Expanding on Marilyn Frye's "Oppression" - Bailey, A. (JOURNAL OF SOCIAL PHILOSOPHY -AUGUSTA-, 1998)
This essay serves as both a response and embellishment of Marilyn Frye's now classic essay " Oppression." It is meant to pick up where this essay left off and to make connections between oppression, as Frye defines it, and the privileges that result from institutional structures. This essay tries to clarify one meaning of privilege that is lost in philosophical discussions of injustice. I develop a distinction between unearned privileges and earned advantages. Clarifying the meaning of privilege as unearned structural advantage makes visible the role white privilege plays in maintaining complex systems of domination such as racism, sexism, heterosexism and classism. Using a critical reading of both Frye and Young's accounts of oppression as a springboard, I develop a definition of privilege as a particular class of unearned advantages. -/- I distinguish my account of privilege from standard legal and philosophical definitions of privilege. The general distinction I make between privileges and advantages rests on three interrelated claims: that benefits granted by privilege are always unearned and conferred systemically to members of dominant social groups; that privileges granted to members of dominant groups solely on the basis of their membership in these groups is never justifiable; and, that privileges have an unconditional value that can be explained not only in terms of immunities, but also in terms of additional benefits
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; justice sociale; phi4336; philosophie; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Des droits à reconnaître: les lesbiennes face à la discrimination - Bonneau, Micheline; Demczuk, Irène (Les éditions du remue-ménage, 1998)
Regroupant recherches et analyses, témoignages et récits personnels, ce livre rend compte de la discrimination vécue par les lesbiennes. Malgré que le Québec ait adopté une Charte des droits de la personne qui interdit toute discrimination basée sur l'orientation sexuelle, il faut reconnaître que l'adoption de ce principe d'équité n'a pas fait disparaître toute trace d'hétérosexisme dans la société. Les lesbiennes ne bénéficient pas encore d'une égalité juridique formelle, encore moins réelle.
Section: 214 pages ; 23 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; lesbophobie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists – including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan – whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

La contribution des femmes à l’histoire de la musique au Québec - Lefebvre, Marie-Thérèse (New Sound, 1998)
Lors d'un colloque international sur les femmes et la création musicale organise par I'Unesco en mars 1996, Mme Zaimont et Mme Ostleitner des Etats-Unis et de I'Autriche, ont démontre dans leur conférence respective á quel point la vie musicale des pays qu'elles représente est encore puissamment dominée par les forces conservatrices et traditionnelles I'Autriche plie sous le poids d'un héritage musical ancestral alors que les Etats-Unis (et jusqu'a un certain point le Canada anglophone) vit actuellement au rythme des tendances politiques de droite. Plusieurs des acquis du mouvement féministe sont actuellement remis en question dans les milieux décisionnels et on ne peut que s'inquiéter de I' impact que pourraient avoir ces mouvements conservateurs sur la création musicale des femmes de ce pays. Mais dans ce même colloque, nous avons également pu entendre les propos de représentantes d'autres pays, je pense ici a la Corée au Japon, a la Bolivie, a I'Uruguay ou les femmes prennent une place de plus en plus importante dans le discours musical et dans la production artistique. De son cote, Le Québec, peut-être a cause de sa situation linguistique et culturelle minoritaire, a développe au cours de son histoire une vitalité artistique enviable et a été a I'avant-garde dans plusieurs domaines dont la création musicale. Le réseau de solidarité que les femmes ont bâti dans le milieu musical depuis quelques années et la place que les compositrices occupent aujourd'hui témoignent de cette vitalité.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; discipline; femmes* artistes; femmes* compositrices; histoire; histoire des femmes*; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Section: xi, 365 pages ; 24 cm
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

Crise et mutation du dispositif de la différence des sexes : regard sociologique sur l'éclatement de la catégorie sexe - St-Hilaire, Colette (Les limites de l'identité sexuelle, 1998)
Keywords: 1900-1999; 1990-1999; amériques; cours; cycles supérieurs; différence des sexes; discipline; fem1000; fem7000; lit3220; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie

Lessons from the damned: queers, whores, and junkies respond to AIDS - Stoller, Nancy E. (Routledge, 1998)
"Lessons from the Damned challenges the notion that public health theories and official organizations have the greatest impact on the fight against AIDS. Instead, Stoller looks closely at the ways the most disenfranchised - the poor, people of color, drug users, gay men and lesbians, and women - have built social movements to fight the epidemic. Drawing upon extensive ethnographic research and the words of the activists themselves, as well as the literature of social movements and theories of bureaucracy, Stoller offers guidelines for dealing with diversity and conflict and also with both theoretical and practical perspectives on cross-community and international organizing."–BOOK JACKET.
Section: xvi, 175 pages : illustrations ; 24 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; capitalisme; care; cours; discipline; histoire et politique; hétérosexisme; justice sociale; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; sida; soc2014; sociologie; sofia; systèmes d'oppressions; thématiques; états-unis

L'art de la récupération des médias dans Médias et féminismes: minoritaires sans paroles - Yamani, Myriame el (Médias et féminismes: minoritaires sans paroles, 1998)
Les médias, s'ils informent, ne servent plus à communiquer. C'est pourquoi cet essai veut répondre à une double question : comment et pourquoi les minoritaires, et les femmes en particulier, s'ils prennent parfois la parole dans le champ médiatique en créant leurs propres journaux, ne peuvent pas la garder ? Comment et pourquoi les médias majoritaires ne rendent-ils pas compte de ces points de vue de minoritaires, en particulier lors d'événements qui les concernent ?
Section: 268 p. : ill. ; 22 cm
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; canada; cours; discipline; médias; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail; travail social; trs1205